mRNA therapy for myocardial infarction: A review of targets and delivery vehicles - Wang, Xinming; Wu, Douglas H.; Senyo, Samuel E. (Frontiers in Bioengineering and Biotechnology, 2022)
Cardiovascular diseases are the leading cause of death in the world. This is partly due to the low regenerative capacity of adult hearts. mRNA therapy is a promising approach under development for cardiac diseases. In mRNA therapy, expression of the target protein is modulated by delivering synthetic mRNA. mRNA therapy benefits cardiac regeneration by increasing cardiomyocyte proliferation, reducing fibrosis, and promoting angiogenesis. Because mRNA is translated in the cytoplasm, the delivery efficiency of mRNA into the cytoplasm and nucleus significantly affects its therapeutic efficacy. To improve delivery efficiency, non-viral vehicles such as lipid nanoparticles have been developed. Non-viral vehicles can protect mRNA from enzymatic degradation and facilitate the cellular internalization of mRNA. In addition to non-viral vehicles, viral vectors have been designed to deliver mRNA templates into cardiac cells. This article reviews lipid nanoparticles, polymer nanoparticles, and viral vectors that have been utilized to deliver mRNA into the heart. Because of the growing interest in lipid nanoparticles, recent advances in lipid nanoparticles designed for cardiac mRNA delivery are discussed. Besides, potential targets of mRNA therapy for myocardial infarction are discussed. Gene therapies that have been investigated in patients with cardiac diseases are analyzed. Reviewing mRNA therapy from a clinically relevant perspective can reveal needs for future investigations.